New Zinc Catalyst for Hydrosilylation of Carbonyl Compounds - Alshakova, Iryna D.; Nikonov, Georgii I. (Synthesis, 2019)
A new zinc complex was synthesized and applied in the catalytic hydrosilylation of carbonyl compounds. Optimization of the reaction conditions showed that the presence a substoichiometric amount of methanol accelerates the process significantly. The reaction can proceed at very low catalyst load (down to 0.1 mol%) under mild reaction conditions. The reaction tolerates the presence of C=C bonds, and thus can be useful for the synthesis of allylic alcohols from α,β-unsaturated aldehydes and ketones.
Keywords: zinc; catalysis; hydrosilylation; aldehydes; ketones; alcohols